Efeitos a longo prazo da aplicação de altas doses de gesso nas características químicas em perfil de latossolo cultivado com café - Ferraz, Raul Magalhães (2017)
Coffee cultivation on Latosols of the Cerrado region in Minas Gerais has been expanded over the years due to the better mechanization condition of these soils. Prior to planting, these soils need to be limed and amended with gypsum, in order to correct aluminum toxicity as well as calcium deficiency in deeper soil layers. Gypsum is considered a soil conditioner as it favors root to grow deeper. However, high doses of gypsum may lead to base imbalance in the soil, mainly regarding to Mg and K leaching as sulphates. This study aimed to evaluate the long-term effect of the high doses gypsum in a commercial coffee plantation in the fisiografic region of the Alto São Francisco, where some farmers have choosen to apply high doses of gypsum. An experiment was established using 4 doses of gypsum (0 t ha-1, 7 t ha-1,14 t ha-1 e 56 t ha-1, applied in the coffee line) and 3 replicates. Soil was sample dat 76 months after the gypsum application. To assess the soil profile, soil samples were taken in the following dephs: 0.15 to 0.25 m, 0.35 to 0.45 m, 0.75 to 0.85, 1.25 to 1.35 m, 1.65 to 1.85 m, and 2.25 to 2.45 m. We evaluated, in the soil samples and soil solution, the contents of Ca2+, Mg2+, K+, SO42-, and the pH. Higher values of Ca2+ and SO42-were found in the treatment with 56 t ha-1. Potassium was found down to approximately 0.80 m, and higher contents were verified in the surface layers for all gypsum treataments. Magnesium vary thought the soil profile, with higher content in deeper layer for the treatment with 56 t ha-1, where pH values were also higher. With the present study, it was possible to find that the Ca2+ and SO42- contents increase significantly, while Mg and K decreased in the surface soil layers, when gypsum was applied in high doses. Therefore, the application of high doses of gypsum may cause imbalances among Ca2+, Mg2+, and K+, which can result in losts of plant nutrition. Thus, future studies, in order to assess the real benefits/damages that high gypsum doses can causes in plant yields, are still required.